A revision of the trapdoor spider genus Liphistius (Mesothelae: Liphistiidae) in Peninsular Malaysia; part 2 - Schwendinger, Peter J.; Syuhadah, Nurul; Lehmann-Graber, Christina; Price, Liz; Huber, Siegfried; Hashim, Rosli; Bhassu, Subha; Monod, Lionel (Museum d'Histoire Naturelle de Geneve, 2019)
The currently known species of the Liphistius trang-growp in Peninsular Malaysia are revised on the basis of genital morphology and an identification key is given. Liphistius thaleban Schwendinger, 1990 and L. rufipes Schwendinger, 1995 are placed in the synonymy of L. yangae Platnick & Sedgwick, 1984. The previously unknown male of L. kanthan Platnick, in Platnick et al., 1997 is described for the first time. Liphistius kanthan and L. tempurung Platnick, in Platnick et al., 1997 are reported to occur together at the Tempurung Cave. Liphistius buran Schwendinger, sp. nov, an island species with a novel character of the palpal organ, is described from males and females. Information on and illustrations of intraspecific variation in most of these species is given together with data on biology and distribution. For selected Liphistius species in Malaysia a phylogenetic tree based on an analysis of COI sequences is presented and discussed in comparison with relationships inferred from morphological characters. Molecular data confirm the distinction between the malayanus-group and the trang-group in Malaysia, but, unlike an earlier interpretation of morphological evolution of genitalia, place species of the trang-group as basal to the malayanus-group. © 2019 Museum d'Histoire Naturelle de Geneve. All rights reserved.